Adenosine Triphosphate Promotes Allergen-Induced Airway Inflammation and Th17 Cell Polarization in Neutrophilic Asthma. (25th May 2017) - Zhang, Fang; Su, Xin; Huang, Gang; Xin, Xiao-Feng; Cao, E-Hong; Shi, Yi; Song, Yong
Abstract : Adenosine triphosphate (ATP) is a key mediator to alert the immune dysfunction by acting on P2 receptors. Here, we found that allergen challenge caused an increase of ATP secretion in a murine model of neutrophilic asthma, which correlated well with neutrophil counts and interleukin-17 production. When ATP signaling was blocked by intratracheal administration of the ATP receptor antagonist suramin before challenge, neutrophilic airway inflammation, airway hyperresponsiveness, and Th17-type responses were reduced significantly. Also, neutrophilic inflammation was abrogated when airway ATP levels were locally neutralized using apyrase. Furthermore, ATP promoted the Th17 polarization of splenic CD4 + T cells from DO11.10 mice in vitro. In addition, ovalbumin (OVA) challenge induced neutrophilic inflammation and Th17 polarization in DO11.10 mice, whereas administration of suramin before challenge alleviated these parameters. Thus, ATP may serve as a marker of neutrophilic asthma, and local blockade of ATP signaling might provide an alternative method to prevent Th17-mediated airway inflammation in neutrophilic asthma.